Toward developing a scoring system for dengue fever in children - Sanikam , Hareesh; Bheeman, Basavaraj; Ramabhatta , Sujatha; Pushpalatha Kariyappa (Asian Journal of Medical Sciences, 2023)
Background: Dengue is a rapidly increasing global public health problem especially in tropical countries. Dengue is a benign and self-limiting febrile illness in the majority of children but in some children, it can progress to severe dengue (SD) resulting in shock, hemorrhage, and death. Aims and Objectives: The aims of this study were to develop a scoring system to predict dengue infection severity. Materials and Methods: This prospective and observational study was conducted on all children admitted with dengue fever at a tertiary teaching institute in India. Daily scoring was done for pulse rate, respiratory rate, blood pressure, hematocrit, platelet count (scores 1–3), and systemic complications (0 if absent, 3 if present). Then, highest score recorded during the hospitalization period was taken for statistical analysis. Results: A total of 194 cases were classified into probable dengue (PD) 134 (69.1%), dengue with warning signs (DWS) 41 (21.1%), and SD 19 (9.8%) as per the WHO 2009 classification. Mean age of presentation was 11.5 years. The most common presenting symptoms were fever (97.9%), vomiting (73.1%) and signs noticed were flushing (63.4%), hepatomegaly (34.5%), and periorbital puffiness (27.3%). Among 134 children with PD, 116 (86.5%) had dengue severity score 5–6, with only 18 (13.5%) had score 7–13, whereas all 60 (100%) children with DWS and SD had score 7–13, none of them had score <7. Hence, a severity score of >7 identified all children with DWS and SD with overestimation in 13.5% children with PD. Conclusion: Daily dengue severity score of >7 indicates the high probability of DWS and SD. However, this scoring system should be validated by similar studies in different settings before we can apply in routine clinical practice.